Photoacoustic imaging of cancer cells with glycol-chitosan-coated gold nanoparticles as contrast agents - Sun, In-Cheol; Ahn, Cheol-Hee; Kim, Kwangmeyung; Emelianov, Stanislav (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2019)
Utility of glycol-chitosan-coated gold nanoparticles (GC-AuNPs) as a photoacoustic contrast agent for cancer cell imaging was demonstrated. Through the synergistic effect of glycol chitosan and gold nanoparticles, GC-AuNPs showed cellular uptake in breast cancer cells and resulted in strong photoacoustic signals in tissue-mimicking cell phantoms. The performance of GC-AuNPs as contrast agents was established with photoacoustic imaging and confirmed with dark-field microscopy. The cell phantoms displayed strong photoacoustic signals if cells were incubated more than 3 h with GC-AuNPs, compared with PEG-AuNPs that showed no photoacoustic signal increase. The enhanced photoacoustic signals originated from the plasmon coupling effect of GC-AuNPs after the cellular uptake in cancer cells. Importantly, photoacoustic imaging of cancer cells was achieved with GC-AuNPs-contrast agents that did not require antibodies or complex surface modification. The endocytosis of GC-AuNPs was also confirmed with dark-field microscopy. The results show that GC-AuNPs have potential as a photoacoustic contrast agent for cellular imaging including tumor tissue imaging. (C) The Authors. Published by SPIE under a Creative Commons Attribution 4.0 Unported License.
Keywords: ULTRASOUND; CARRIERS